Imaginary representations of the city and the village in ivorian children’s books - Dangui, Nadia (Ondina - Ondine, 2022)
In Africa, children’s books are a marginalised genre. However, they serve as a means of communication and a means for transmitting values and standards of conduct in a given culture. Thus, they can be used for the education and socialisation of children. Authors inject into the children’s books a set of representations of the society that children must know, recognize and assimilate. How, in this perspective, is the village imagined and represented in children’s books in relation to the city? The aim of this paper is to study the imaginary representations that authors of Ivorian children’s books make of the village as a place of destination. A lexical and thematic content analysis and a semiological analysis were conducted on a corpus of 35 Ivorian children’s books. The books studied present the village as a place of tranquillity, rest and peace compared to the noisy city full of nauseating odours. Keywords : City, village, children’s book, Côte d’Ivoire, imagination